Thermodynamic properties of temozolomide in crystalline and gaseous aggregate states - Yurkshtovich, Yana N.; Blokhin, Andrey V. (Journal of the Belarusian State University. Chemistry, 2022)
Temozolomide (4-methyl-5-oxo-2,3,4,6,8-pentazabicyclo[4,3,0]nona-2,7,9-triene-9-carboxamide) is an active component of antitumor immunosuppressive alkylating drugs, and it used largely for the treatment of various types of malignant tumors, including malignant gliomas that are difficult to treat by surgery (glioblastoma multiforme and anaplastic astrocytoma). Wide field of temozolomide application dictates the need for its comprehensive thermodynamic study. In this work temperature dependance of the temozolomide heat capacity was obtained using the adiabatic calorimetry method and the standard thermodynamic functions of crystalline temozolomide were calculated in the temperature range 80–370 K. Standard thermodynamic functions of the temozolomide in the ideal gas state were calculated using the statistical thermodynamics approach in the temperature range 0–1000 K. To obtain the standard internal energy and enthalpies of combustion and formation of crystalline temozolomide at T = 298.15 K the combustion bomb calorimetry was used. Standard enthalpy of formation of the gaseous temozolomide was calculated in the framework of the isodesmic reactions method using quantum chemical computing. To calculate standard sublimation enthalpy of temozolomide the electrostatic potential model was applied. The results obtained can find application in solving problems of optimisation of temozolomide production processes and to validate experimentally obtained values of thermodynamic properties of the temozolomide.
Keywords: temozolomide; thermodynamic properties; heat capacity; enthalpy of formation; enthalpy of combustion; sublimation enthalpy